COVID-19 Patients in Bangladesh: A Qualitative Investigation on Social Exclusions and Stigmatization - Paul, Alak; Jabed, Md Akib; Upama, Romeo Afrin; Zaman, Sifat (The Dhaka University Journal of Earth and Environmental Sciences, 2022)
The COVID-19 pandemic has snatched away the lives and livelihoods of many people throughout the world. The number of infected and death from SARS-CoV-2 has still been increasing in Bangladesh. The fear of the unknown, uncertainty, knowledge gap and high communicability have fed into the social stigmatization of COVID-19 patients and survivors. Considering the research gap, this study looks at how stigma and prejudice caused by COVID-19 are prevailing in Bangladesh. This research was carried out on purposively chosen 200 COVID-19 positive patients who were hospitalized in a government-run COVID-19 dedicated hospital in Dhaka from the end of March 2020 to August 2020. All ethical concerns were maintained during data collection. The qualitative approach was used for in-depth interviewing through telephone. The present study finds some phenomenal examples and experiences of marginalization and stigmatization due to the highly contagious nature of the virus among the patients, relatives, neighbors, health care workers etc. COVID-19 patients or their relatives are found to pass muchstigmatized life with a feeling of hopelessness. Even though many of the COVID-19 patients died, their family members are still bearing the brunt, making them stigmatized. The discourses of self-stigmatization, social harassment, treatment, prejudice, and stigmatized funeral etc., have been discussed critically. The Dhaka University Journal of Earth and Environmental Sciences, Vol. 10(3), Special Issue 2022: 73-84